Effect of Ethyl Acetate Fraction of Avocado Peel (Persea americana Mill.) on Total Cholesterol Levels in Hypercholesterolemic Wistar Rats - Ferdian Adhy Pratama Putra; Ignatius Hapsoro Wisandoko; Rama Samara Brajawikalpa (Yayasan Aliansi Cendekiawan Indonesia Thailand (Indonesian Scholars' Alliance), 2025)
Background: Hypercholesterolemia is a condition that can increase the risk of coronary heart disease, stroke, high blood pressure, obesity and other health problems. The ethyl acetate fraction of avocado peel offers a novel approach by isolating key bioactive compounds while separating them from other components, focusing on the desired properties of compounds such as flavonoids, saponins, and phenolics, which are well-known for their antihyperlipidemic effects. Aims: To analyze the effect of ethyl acetate fraction of avocado peel (Persea americana Mill.) on total cholesterol levels of Wistar white rats with hypercholesterolemia. Methods: This study was experimental with a pre and post test with control group design using 20 male white rats (Rattus norvegicus) of the Wistar strain that had been fed high-fat feed for 14 days and divided into 5 groups for 7 days of treatment, namely the negative control group that was given only high-fat feed, the positive control group that was given the drug simvastatin 0.18 mg/200gBW, and 3 treatment groups that were given the ethyl acetate fraction of avocado peel with a tiered dose of 100 mg/KgBW, 75 mg/KgBW, and 50 mg/kgBW. The data were analyzed using a one-way ANOVA test with a post hoc test Results: The ethyl acetate fraction of avocado fruit peel positively contains alkaloids, flavonoids, phenolics, saponins, tannins, and triterpenoids or steroids. The average reduction in total cholesterol levels is 19.5 mg/dL (p < 0.05) at a dose of 100 mg/kgBW, 17.5 mg/dL (p < 0.05) at a dose of 75 mg/kgBW, and 13 mg/dL (p < 0.05) at a dose of 50 mg/kgBW. Conclusion: The ethyl acetate fraction of avocado peel is effective in reducing total cholesterol levels with an effective dose of 100 mg/kgBW. With an effective dose of 100 mg/kg body weight that has been established, subsequent research can focus on the development of more stable and efficient formulations for clinical applications. The effect of lowering cholesterol levels is associated with the content of secondary metabolite compounds contained in the ethyl acetate fraction of avocado peels, namely flavonoids, phenolics, saponins, tannins, triterpenoids and steroids.